Comprehensive Management of Preseptal Cellulitis with Massive Palpebral Abscess in 72-year-old Man - Ruth Anastasia; Ismi Zuhria; Susy Fatmariyanti (Universitas Airlangga, 2022)
Introduction: Infectious inflammation of the periorbital and orbital soft tissue can be classified as preseptal (periorbital) or postseptal (orbital) cellulitis. Eyelid abscess, an accumulation of pus in the palpebral tissue, can occur in isolation or in association with preseptal cellulitis. Preseptal cellulitis is nearly three times more common than orbital cellulitis. Case Presentation: The patient, in this case, was admitted with a complaint of swollen left eyelid ten days before being admitted. Swollen eyelid with the inability to open the left eye was accompanied by pus discharge five days before coming to the hospital. Current complaints include eyelid pain, swelling, and discharge of thick yellow fluid. Massive abscess with active pus and crust was present in the left superior and inferior eyelid and frontotemporal area. A head CT scan revealed a soft tissue mass in the left sub galea soft tissue, left frontal region, left orbit, and left temporal region. Multi-department consultations and several workups were done to reveal the etiology and plan the appropriate management of this condition. Conclusion: A comprehensive assessment must be done to distinguish preseptal and orbital cellulitis. Ophthalmology examination and imaging are crucial to detect any extension of the palpebral abscess beyond the orbital septum. Examining an immunocompromised state and focal infection is crucial in determining proper treatment.